A three-armed cryptand with triazine and pyridine units: synthesis, structure and complexation with polycyclic aromatic compounds - Lar, Claudia; Woiczechowski-Pop, Adrian; Bende, Attila; Grosu, Ioana Georgeta; Miklášová, Natalia; Bogdan, Elena; Hădade, Niculina Daniela; Terec, Anamaria; Grosu, Ion (Beilstein Journal of Organic Chemistry, 2018)
The aromatic nucleophilic substitution reaction based synthesis of a three-armed cryptand displaying 2,4,6-triphenyl-1,3,5-triazine units as caps and pyridine rings in the bridges, along with NMR, MS and molecular modelling-based structural analysis of this compound are reported. Appropriate NMR and molecular modelling investigations proved the formation of 1:1 host–guest assemblies between the investigated cryptand and some polynuclear aromatic hydrocarbons or their derivatives.
Keywords: aromatic guests; aromatic nucleophilic substitution; cryptand; NMR titration; 1,3,5-triazine